2017
DOI: 10.1038/s41467-017-00374-1
|View full text |Cite
|
Sign up to set email alerts
|

Whi7 is an unstable cell-cycle repressor of the Start transcriptional program

Abstract: Start is the main decision point in eukaryotic cell cycle in which cells commit to a new round of cell division. It involves the irreversible activation of a transcriptional program by G1 CDK-cyclin complexes through the inactivation of Start transcriptional repressors, Whi5 in yeast or Rb in mammals. Here we provide novel keys of how Whi7, a protein related at sequence level to Whi5, represses Start. Whi7 is an unstable protein, degraded by the SCFGrr1 ubiquitin-ligase, whose stability is cell cycle regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…This could explain some functional differences, such as the fact that Whi5 is the repressor that plays the most important role in the control of Start in normal conditions. We have previously reported that WHI7 overexpression rescues the cell size defect of a whi5 mutant (Gomar-Alba et al, 2017), which could support this idea. However, it is necessary to consider that this overexpression was accomplished using the very strong GAL1 promoter.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This could explain some functional differences, such as the fact that Whi5 is the repressor that plays the most important role in the control of Start in normal conditions. We have previously reported that WHI7 overexpression rescues the cell size defect of a whi5 mutant (Gomar-Alba et al, 2017), which could support this idea. However, it is necessary to consider that this overexpression was accomplished using the very strong GAL1 promoter.…”
Section: Discussionsupporting
confidence: 58%
“…Whi7 (also known as Srl3), Whi5 and Nrm1 constitute a family of proteins characterized by the presence of a GTB (G1/S transcription binding factor) motif ( Travesa et al, 2013 ). WHI7 gene expression is induced in different situations of cellular stress ( Garcia et al, 2004 ; Gasch et al, 2000 ; Waern and Snyder, 2013 ), and Whi7 protein is unstable, being degraded by the SCF Grr1 ubiquitin ligase in a Cdc28-dependent and cell cycle-regulated way ( Gomar-Alba et al, 2017 ). Unlike whi5 mutation, whi7 mutation has no effect on cell size distribution in exponentially growing cultures, questioning a role for this protein at the beginning of the cell cycle ( Costanzo et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCF Grr1 is necessary for degradation of the mediator component Med3 ( Gonzalez et al ., 2014 ), as well as proteins regulating the glycolytic–gluconeogenic switch ( Benanti et al ., 2007 ). More recently, it has also been shown to regulate Whi7, a repressor of Start transcriptional gene expression ( Gomar-Alba et al ., 2017 ). To determine whether SCF Grr1 plays a role in H 2 O 2 -induced Med13 degradation, we examined Med13 protein levels following 0.4 mM H 2 O 2 treatment in wild-type and grr1∆ cells harboring functional Med13-HA on a single copy plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative RT-PCR (qPCR) experiments were carried out to determine the changes in mRNA levels. Total RNA and cDNA were prepared as described in Gomar-Alba et al [59].…”
Section: Gene Expression Analysismentioning
confidence: 99%